The allocation of resources to livestock research in Africa - Toulmin, C. (International Livestock Centre for Africa, 1985)
Looks at the allocation of resources to livestock research in Africa. Assesses the role of agricultural research and its value to national governments. Investigates the appropriate criteria to use for decision making by comparing three kinds of decision-making models. Presents conclusions for policy-making.